Marine derived compounds as binders of the White spot syndrome virus VP28 envelope protein: In silico insights from molecular dynamics and binding free energy calculations. (October 2016) - Sivakumar, K.C.; Sajeevan, T.P.; Bright Singh, I.S.
Graphical abstract: Highlights: A virtual library of 388 marine bioactive compounds extracted from literatures published in Marine drugs Journal published by MDPI was used in this study. The top ranking compounds from docking were chosen from the flexible docking based on the binding affinities (ΔGb). In addition, the MD simulation and binding free energy analysis were implemented to validate and capture intermolecular interactions. The results suggested that two compounds obtained a negative binding free energy with −40.453 KJ/mol and −31.031 KJ/mol for compounds with ids 30797199 and 144162 respectively. The RMSD curve indicates 30797199 moves into the hydrophobic core, while the position of 144162 atoms changes abruptly during the simulation and is mostly stabilized by water bridges. The shift in RMSD values of VP28 corresponding to ligand RMSD gives an insight into the ligand induced conformational changes in the protein. This study is first of its kind to elucidate the explicit binding of chemical inhibitor to WSSV major structural protein VP28. Abstract: White spot syndrome virus (WSSV) remains as one of the most dreadful pathogen of the shrimp aquaculture industry owing to its high virulence. The cumulative mortality reaches up to 100% within in 2–10 days in a shrimp farm. Currently, no chemotherapeutics are available to control WSSV. The viral envelope protein, VP28, located on the surface of the virus particle acts as a vital virulence factor in the initial phases of inherent WSSV infection in shrimp. Hence, inhibition of envelope protein VP28 could be a novel way to deal with infection by inhibiting its interaction in the endocytic pathway. In this direction, a timely attempt was made to recognize a potential drug candidate of marine origin against WSSV using VP28 as a target by employing in silico docking and molecular dynamic simulations. A virtual library of 388 marine bioactive compounds was extracted from reports published in Marine Drugs . The top ranking compounds from docking studies were chosen from the flexible docking based on the binding affinities (ΔGb). In addition, the MD simulation and binding free energy analysis were implemented to validate and capture intermolecular interactions. The results suggested that the two compounds obtained a negative binding free energy with −40.453 kJ/mol and −31.031 kJ/mol for compounds with IDs 30797199 and 144162 respectively. The RMSD curve indicated that 30797199 moves into the hydrophobic core, while the position of 144162 atoms changes abruptly during simulation and is mostly stabilized by water bridges. The shift in RMSD values of VP28 corresponding to ligand RMSD gives an insight into the ligand induced conformational changes in the protein. This study is first of its kind to elucidate the explicit binding of chemical inhibitor to WSSV major structural protein VP28.